Le Counselling de Groupe Avec les Enseignants Effet du "C Group" sur le Self-Concept de l’Étudiant - Devinante, Simone (Canadian Journal of Counselling and Psychotherapy, 2012)
The objectives of this research were to determine whether use of the "C Group" technique, with its origin in Adlerian theory, would improve teachers' attitudes in interpersonal relations with their students, and whether this technique would cause a positive change in the students' self-concepts. An experimental group and a control group were establised. The experimental group participated in "C Group" sessions weekly for twelve weeks. The results of statistical analysis of the data were that students of "C Group" participants achieved a positive change both in their perceptions of their teachers and in self-concept. An additional result was that teacher attitudes and self-concepts were improved.